UNILATERAL BARTHOLIN’SGLAND CYST IN A JERSEY CROSSBRED COW - SOUNDARARAJAN, C; PRAKASH, M ARUL; KUMAR, K SENTHIL (The Indian Journal of Animal Reproduction, 2023)
A case of unilateral Bartholin’s gland cyst in crossbred Jersey cattle is reported.